2010
DOI: 10.1007/s10397-010-0640-x
|View full text |Cite
|
Sign up to set email alerts
|

Uterovaginal anastomosis for the management of congenital atresia of the uterine cervix

Abstract: Congenital atresia of the cervix is a rare mullerian anomaly. Hysterectomy has been advocated as the management of choice in the early days as the reproductive performance is thought to be low despite successful neo-canal creation. In recent years, conservative surgery is being recommended more frequently in patients with congenital cervical atresia and with total or partial vaginal aplasia and is shown to have a better reproductive performance. The treatment strategy should be tailored to relieve retrograde m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…3 When cervical reconstruction is not feasible, uterovaginal anastomosis is preferred and recently being recommended over other alternatives as the first treatment option, as it has a lower risk of restenosis, and successful reproductive outcomes have been reported with fewer complications. 9 10 The earliest series on uterovaginal anastomosis technique described by Deffarges et al 11 reported successful creation of outflow channel in 18 patients with failure due to restenosis in only 1 woman. They also reported six spontaneous conceptions in four of these women who delivered between 36 and 38 weeks' gestation via cesarean section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 When cervical reconstruction is not feasible, uterovaginal anastomosis is preferred and recently being recommended over other alternatives as the first treatment option, as it has a lower risk of restenosis, and successful reproductive outcomes have been reported with fewer complications. 9 10 The earliest series on uterovaginal anastomosis technique described by Deffarges et al 11 reported successful creation of outflow channel in 18 patients with failure due to restenosis in only 1 woman. They also reported six spontaneous conceptions in four of these women who delivered between 36 and 38 weeks' gestation via cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, many successful open and laparoscopic approaches to uterovestibular anastomosis for cervicovaginal aplasia have been reported with good functional and reproductive outcomes. 9 10 12 13 14 15 16 17 Interestingly, mucinous secretions such as normal endocervical gland secretions have been noted during follow-up in patients, suggesting metaplasia of the most caudal endometrial glands in the neouterovaginal channel. 10 This possibly explains fewer rates of ascending upper genital tract infections reported in patients who undergo uterovaginal anastomosis.…”
Section: Discussionmentioning
confidence: 99%